INFORMATION, KEY ELEMENT OF ACCOUNTING AND AUDIT IN THE KNOWLEDGE SOCIETY - NELUTA MITEA (Challenges of the Knowledge Society, 2011)
In a knowledge society, the advantage of nations will not result from their natural resources, nor to the cheap labor, but from their ability to valorize the intellectual potential and to use efficiently the information. The knowledge based economy represents a new step in the development of human civilization that promises us a better future. The knowledge transfer between people and generations in order to facilitate human society’s evolution is the basic function of information science. This paper aims to examine how, in Romania, accounting and audit use and create information in current conditions of economic development. The purpose of this study consists in offering perspectives of improving the information quality. An information is high quality when, by its form and content, it corresponds integrally to all the needs, the exigencies and expectations of its user, without sacrificing the reality. A number of errors made by the accounting profession have been identified along this paper. These errors led to the decrease of information’s credibility. But the study proposes some changes in order to restore the image of this profession: the changes are sustained by the advantages of Knowledge Economy and Information Society. The research method consists in studying a rich background material, including reference items, such as works of applied and fundamental research. The originality of this work is given by the identification of knowledge society’s challenge which could be used as a lever of revival for accounting and audit in Romania.